Health and wellness tourism from a hospitality viewpoint: quality of services offered in a medical spa - Enói dos Santos, Maria (2022)
The objectives of this study were divided into 4 points: characterization of the chosen spa; services available in the spa; frequency of tourists to the spa and strategies adopted; and analysis of the spa services. This study is classified as exploratory descriptive, with a qualitative, non-probabilistic approach. The checklist used the SERVPERF model, where it is possible to analyze the quality level of the service provided. For the analysis of the services, it was necessary to use the participant observation method – OP, in the pseudo purchase methodology. The research was carried out in a medical spa in Sorocaba, São Paulo, Brazil. The technique used to analyze the answers of the spa collaborators was Content Analysis. It was observed that satisfaction with the attendance, provided service, and available infrastructure, become key elements for functional and positive performance. Was can conclude that hospitality in this medical spa is governed by empathy, attention and compassion with which all guests are treated, this being their differential for client's loyalty.